What Does “Asymmetric VR” Mean? A Directed Content Analysis of Co-Located Use of VR by Users on Reddit - Ouverson, Kaitlyn Michelle; Scherber, Carsten; Oldham, Emily; Gilbert, Stephen B. (Frontiers in Virtual Reality, 2021)
Technology is often framed in terms of space and time of use, such that a mobile phone is used to either send asynchronous messages or host synchronous conversations with remote others, while a classroom smartboard supports co-located, synchronous learning. As the technology becomes more immersive, the applicability of frameworks such as the time/place matrix becomes less clear. This study attempts to provide clarity by applying the Composite framework for Asymmetric VR (CAVR) to online forum descriptions of the use of immersive virtual reality (VR) in co-located groups. A related framework, Roles of Technology, is also explored; however, the authors argue the framework must be expanded before application of it beyond mobile technology. To better understand one possible solution to co-located VR’s isolation problem, a directed content analysis was conducted, exploring the discussion of co-located and asymmetric VR use on various subreddits. As a result, 11 patterns of co-located use of VR, including 8 which specify asymmetric VR designs, are identified. The researchers update the dimensions of CAVR according to these results, compare CAVR to another nascent framework, and offer suggestions for future work and applicability to practice. This work is intended to help guide future creation and research of asymmetric VR experiences through the deconstruction of asymmetric VR experiences to their key parts via the application of CAVR.